The Saturation of Learning Online during a Pandemic - Nabila, Sarah; Saptadi, Heri; Dyah Yuli, Padmi (Bisma The Journal of Counseling, 2022)
This research was motivated by many students who experienced boredom during online learning that occurred in Indonesia, including at SMP Negeri 39 Semarang. The purpose of this study was to determine the learning process during the pandemic, the obstacles and causes of students experiencing boredom in online learning in class VIII A and VIII I of SMP Negeri 39 Semarang. This study uses a qualitative method with a descriptive phenomenological research approach. Sources of data in this study are interviews, observation and documentation. The informants in this study were 4 students as primary and 2 teachers as objects. The data analysis technique uses an interactive analysis model. The results of this study indicate that class VIII A and VIII I SMP Negeri 39 Semarang experience online learning boredom during the pandemic due to various causal factors shown by students, one of which is the learning method that does not vary, learning is monotonous and many school assignments. Based on this, it can be suggested that the implementation of the online learning process should use varied learning methods so that students do not feel bored while studying and can arouse students' enthusiasm in participating in online learning.